Modeling the effects of physical activity, education, health, and subjective wealth on happiness based on Indonesian national survey data - Bhina Patria (BMC, 2022)
Abstract Background Studies on physical activity's psychological benefits are generally fewer than those on its physiological benefits, and these limited studies have mostly investigated its impact on cognitive functions. Studies exclusively investigating physical activity's effects on happiness are rare. This study aims to investigate the effect of physical activity on psychological functions, especially on happiness. Methods Analysis was based on a large field of nationally representative Indonesian adult data. Data were compiled based on face-to-face interviews with 12,051 adults. Participants provided measures of physical activity, subjective health, and happiness, and responses were recorded with computer-assisted personal interviewing (CAPI) software. Demographic data, including gender, subjective wealth, education, and age, were also included in the analysis. Structural equation modeling (SEM) was conducted to determine the relationship between physical activity, health, subjective wealth, and happiness. Results The tested model of the association between physical activity, health, subjective wealth, and happiness indicated a good fit, based on χ 2 (1, n = 12,051) = 48.733, p = .001, RMSEA = .063, and CFI = .97. Path analysis results showed that health conditions mediated the effects of physical activity on happiness. The result also showed positive effects of education level and subjective wealth on happiness. Conclusion This study provides evidence that engagement in physical activity has a positive impact on happiness. Indonesian adults should engage in more active lifestyles since more than one-third of Indonesians did not get enough physical activity.